The Limits of Identity : Politics and Poetics in Latin America - Hatfield, Charles Dean, 1977- (Book collections on Project MUSE., 2015)
The Limits of Identity is a polemical critique of the repudiation of universalism and the theoretical commitment to identity and difference embedded in Latin American literary and cultural studies. Through original readings of foundational Latin American thinkers (such as Jose Martí and Jose Enrique Rodó) and contemporary theorists (such as John Beverley and Doris Sommer), Charles Hatfield reveals and challenges the anti-universalism that informs seemingly disparate theoretical projects. The Limits of Identity offers a critical reexamination of widely held conceptions of culture, ideology, interpretation, and history. The repudiation of universalism, Hatfield argues, creates a set of problems that are both theoretical and political. Even though the recognition of identity and difference is normally thought to be a form of resistance, The Limits of Identity claims that, in fact, the opposite is true.